Detection of D‐penicillamine in skin lesions in a case of dermal elastosis after a previous long‐term treatment for Wilson's disease. (10th January 2014) - Neri, I.; Gurioli, C.; Raggi, M.A.; Saracino, M.A.; Morganti, E.; Bugamelli, F.; de Ponti, F.; Vaccari, S.; Patrizi, A.; Balestri, R.
Abstract Background Skin adverse events associated with D‐Penicillamine (DPA) are common and multi‐faceted, although the presence of DPA or its metabolites has never been documented in the skin, because of inherent difficulties in determining its tissue levels. Thus, the association between DPA and DPA‐related dermatoses has been only hypothesized on the basis of careful history, clinical observation and typical histopathological findings. Objective To detect DPA in biopsy specimens in a unique case of 25‐year‐late‐onset elastosis perforans serpiginosa and pseudo‐pseudoxanthoma elasticum associated with a history of long‐term high dose DPA, by applying a recently described analytical method to assess the presence of DPA in skin. Methods We used a reliable analytical method based on high‐performance liquid chromatography coupled with amperometric detection to look for the presence of DPA in skin biopsy specimens. Results A chromatographic peak corresponding to DPA was evidenced in some affected skin samples collected from the patient. Conclusion We documented the effective presence and the persistence after 25 years of DPA in the skin of a woman affected by elastotic cutaneous change due to a long‐term therapy with DPA. This report provides further evidence of the relationship between DPA deposit in affected skin and clinical manifestation.